Molecular Profiling of Endometrial Malignancies - Norasate Samarnthai; Kevin Hall; I-Tien Yeh (Obstetrics and Gynecology International)
Molecular profiling of endometrial neoplasms reveals genetic changes in endometrial carcinomas that support the dualistic model, in which type I carcinomas are estrogen-dependent, low grade lesions and type II carcinomas are nonestrogen dependent and high grade. The molecular changes in type I endometrial carcinomas include mutations in PTEN, PIK3CA, KRAS, and 𝛽-catenin, along with microsatellite instability, whereas type II endometrial carcinomas are characterized by genetic alterations in p53, HER2/neu, p16, and E-cadherin. For endometrial neoplasms with a malignant mesenchymal component, C-MYC mutations and loss of heterozygosity are frequently seen in carcinosarcomas, and a fusion gene, JAZF1/JJAZ1, is distinctive for endometrial stromal sarcoma. In addition, p53 mutations may play an important role in tumorigenesis of undifferentiated endometrial sarcoma. These molecular changes can help in the diagnosis of endometrial neoplasms, as well as form the basis of molecular targeted therapy.